CE: Nurses Are More Exhausted Than Ever. Issue 12 (December 2021) - Trinkoff, Alison M.; Baldwin, Carol M.; Chasens, Eileen R.; Dunbar-Jacob, Jacqueline; Geiger-Brown, Jeanne; Imes, Christopher C.; Landis, Carol A.; Patrician, Patricia A.; Redeker, Nancy S.; Rogers, Ann E.; Scott, Linda D.; Todero, Catherine M.; et al.
Abstract : ABSTRACT: For nurses, the challenges posed by demanding work environments and schedules often lead to fatigue, and this can be exacerbated during crises like the COVID-19 pandemic. In this article, the authors discuss causes and challenges of nurse fatigue and consider several evidence-based strategies and solutions for individual nurses and organizations. Barriers to implementation, including a negative workplace culture and inadequate staffing, are also described, and several resources are presented. Abstract : This article discusses causes and challenges of nurse fatigue, evidence-based strategies and solutions for individual nurses and organizations, and changes needed to transform nursing culture and workplaces into more supportive environments for nurses.